(untitled) (International Seven Journal of Health Research, 2024)
The present study aimed to analyze the diagnostic methods provided by the SUS that are carried out in Brazil for the BC and to explain the relevance of these approaches in the early detection of this pathology. This was a longitudinal, retrospective and quantitative study, where data was collected through the SUS Information and Informatics Department (DATASUS), through the Tabnet platform, on the use of diagnostic tests for breast cancer and mammogram results positive for breast injury in the period 2017 to 2021. In addition, data were obtained from the Mortality Information System (SIM) on the breast cancer mortality rate from 2015 to 2019. The study chose the age group of 40 to 59 years for data analysis, as they are the most susceptible ages for the development of MC. In relation to exams carried out between 2017 and 2021, mammography (MMG) is the most used exam with 8,109,591, followed by breast histology with 73,008 in total, and cytology with a lower number of 38, 945. mortality by BC of the female population aged 40 to 59 years, from 2015 to 2019, with 32,561 deaths. The conclusion of this study is that mammography is the exam most used by the Brazilian population for the early diagnosis of MC, but there is a need for new methods to aid in its detection. Another observation identified was the increase in the number of deaths in Brazil over the years.